2020
DOI: 10.1038/s41598-020-62712-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization for EEG channel selection and accurate intruder detection in an EEG-based subject identification system

Abstract: We present a four-objective optimization method for optimal electroencephalographic (eeG) channel selection to provide access to subjects with permission in a system by detecting intruders and identifying the subject. Each instance was represented by four features computed from two subbands, extracted using empirical mode decomposition (eMD) for each channel, and the feature vectors were used as input for one-class/multi-class support vector machines (SVMs). We tested the method on data from the event-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…We previously showed that the TAR and TRR of the models created using OC-SVM can be improved by finding the best nu and gamma parameters 12 . We performed the optimization process defined in the "Methods" section to provide more information about the behavior of OC-SVM models using a bigger dataset, trying to improve the TAR and TRR while reducing the necessary number of EEG channels for subject identification.…”
Section: Channel Selection Using Nsga-iii and Oc-svm For Eeg Signals mentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that the TAR and TRR of the models created using OC-SVM can be improved by finding the best nu and gamma parameters 12 . We performed the optimization process defined in the "Methods" section to provide more information about the behavior of OC-SVM models using a bigger dataset, trying to improve the TAR and TRR while reducing the necessary number of EEG channels for subject identification.…”
Section: Channel Selection Using Nsga-iii and Oc-svm For Eeg Signals mentioning
confidence: 99%
“…For EEG-based biometric systems, several approaches have been presented using various paradigms to stimulate and record the EEG signals, i.e. imagined speech [1][2][3] , resting-state [4][5][6][7][8][9][10] , and event-related potentials (ERPs) 11,12 .…”
mentioning
confidence: 99%
See 3 more Smart Citations